Identifikasi Karakteristik Desa di Provinsi Bengkulu Tahun 2018 Berdasarkan Latent Class Cluster (LCC) - Debora Chrisinta (Seminar Nasional Official Statistics, 2022)
The most basic socio-economic problem in Indonesia at this time is the problem of inequality in economic development. Bengkulu Province is included in the category of 10 poorest provinces in Indonesia. Therefore, it is necessary to analyze the grouping characteristics of each village in Bengkulu Province, so that the government's policy targets are more focused. One of the statistical techniques that can be used to identify village characteristics is cluster analysis, one of which is Latent Class Clustering (LCC). This method is based on data distribution and can be used when the data encountered comes from mixed variables, namely, categorical and numeric. The data used is the Village Potential data in 2018. The variables used are derived from the dimensions of the Village Development Index (VDI). The optimal clusters obtained are 3 clusters, the best clusters are shown in cluster 2 which gives a relatively higher VDI than clusters 1 and 3. The characteristics shown in cluster 2 indicate that villages that have adequate facilities and infrastructure are assessed based on the dimensions of IPD on numerical variables and the categories used. Meanwhile, clusters 1 and 3 have VDI characteristics which tend not to have several facilities or adequate infrastructure.